Adjuvant effect of dendritic cells transduced with recombinant vaccinia virus expressing HPV16-E7 is inhibited by co-expression of IL12 - Mackova, Jana; Kutinova, Luda; Hainz, Petr; Krystofova, Jitka; Sroller, Vojtech; Otahal, Pavel; Gabriel, Pavel; Nemeckova, Sarka (International journal of oncology, 2004)
Dendritic cells (DC) enhanced the immunogenicity of recombinant vaccinia viruses (rVV) expressing the E7 protein of HPV16, a tumor-associated antigen (TAA). Immunization with DC transduced by rVV generated from strain Praha or MVA induced better protection against the growth of transplanted TC-1 tumors in C57Bl/6 mice than did immunization with either of these rVVs administered alone by the same route. Interestingly, DC transduced with a double recombinant vaccinia virus expressing E7 protein together with the Th1-polarizing cytokine IL12, which has been shown to enhance the cellular response in several other systems, induced lower anti-tumor immunity than DC transduced with rVV expressing E7 protein alone. The inhibitory effect mediated by IL12 on immunization with rVV-infected DC was dose-dependent and was observed after immunization with DC transduced with IL12-expressing rVV even at low multiplicity.
Keywords: imunizace; Th1 buňky; Humans; genetické vektory; Adjuvants, Immunologic; dendritické buňky; Neoplasms, Experimental; Transduction, Genetic; onkogenní proteiny virové; adjuvancia imunologická; Female; Genetic Therapy; interleukin-12; lidé; Immunotherapy; Vaccinia virus; zvířata; myši; Oncogene Proteins, Viral; transdukce genetická; myši inbrední C57BL; Mice; genetická terapie; Papillomaviridae; Antigen Presentation; Papillomavirus Infections; Papillomavirus E7 - proteiny; ženské pohlaví; experimentální nádory; protinádorové vakcíny; Dendritic Cells; Interleukin-12; Cancer Vaccines; Mice, Inbred C57BL; Th1 Cells; infekce papilomavirem; Genetic Vectors; Animals; míra přežití; virus vakcinie; imunoterapie; Papillomavirus E7 Proteins; Immunization; prezentace antigenu; Survival Rate